2019
DOI: 10.1074/jbc.ra118.006006
|View full text |Cite
|
Sign up to set email alerts
|

Replication protein A (RPA) sumoylation positively influences the DNA damage checkpoint response in yeast

Abstract: The DNA damage response relies on protein modifications to elicit physiological changes required for coping with genotoxic conditions. Besides canonical DNA damage checkpointmediated phosphorylation, DNA damage-induced sumoylation has recently been shown to promote genotoxin survival. Crosstalk between these two pathways exists in both yeast and human cells. In particular, sumoylation is required for optimal checkpoint function, but the underlying mechanisms are not wellunderstood. To address this question, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 45 publications
4
32
0
Order By: Relevance
“…RPA, which is composed of Rfa1-3 subunits, was also of interest because it binds to ssDNA at the collapsed fork and has several mono-sumoylation sites. We recently defined four Rfa1 sumoylation sites and showed that mutating these four lysines (rfa1-K170, −180, −411, and −427R or rfa1-4KR) largely eliminated Rfa1 sumoylation (Dhingra et al, 2019). We also confirmed that mutating the previously identified sumoylation sites on Rfa2 (rfa2-K199R) and Rfa3 (rfa3-K46R) (Psakhye and Jentsch, 2012) greatly reduced the sumoylation of these proteins.…”
Section: Loss Of Rad52 Rad59supporting
confidence: 72%
See 2 more Smart Citations
“…RPA, which is composed of Rfa1-3 subunits, was also of interest because it binds to ssDNA at the collapsed fork and has several mono-sumoylation sites. We recently defined four Rfa1 sumoylation sites and showed that mutating these four lysines (rfa1-K170, −180, −411, and −427R or rfa1-4KR) largely eliminated Rfa1 sumoylation (Dhingra et al, 2019). We also confirmed that mutating the previously identified sumoylation sites on Rfa2 (rfa2-K199R) and Rfa3 (rfa3-K46R) (Psakhye and Jentsch, 2012) greatly reduced the sumoylation of these proteins.…”
Section: Loss Of Rad52 Rad59supporting
confidence: 72%
“…Freudenreich lab strains are listed in Table S9 and had either W303 or BY4705 backgrounds. Several point mutant alleles used here have been previously characterized: pSLX5 SIM1234 (Xie et al, 2007), smx3-331, smt3-3KR, mms21-11 (Bustard et al, 2016), rad52-3KR, rad59-2KR (Silva et al, 2016), rpa-6KR (Dhingra et al, 2019), rad52-smt3ΔGG, rad59-smt3ΔGG (Silva et al, 2016), mre11-D56N (Moreau et al, 1999), mre11-3 (Bressan et al, 1998;Tittel-Elmer et al, 2009), and nse5-ts1 . The smc5-smt3 and rfa1-smt3 mutants were generated by transformation of a SMT3-KANMX fragment such that Smt3 with a stop codon was fused to the C-terminal end of Smc5 and Rfa1 respectively.…”
Section: Methods Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, DNA damage-induced sumoylation and checkpoint activation are largely separable, albeit with some degree of crosstalk (Cremona et al 2012;Wu et al 2014). For example, eliminating the main checkpoint kinase Mec1 in yeast does not reduce bulk sumoylation, but the sumoylation of the ATRIP checkpoint protein in human cells and RPA in yeast positively affects checkpoint function (Cremona et al 2012;Wu et al 2014;Dhingra et al 2019).…”
Section: Sumo E3smentioning
confidence: 99%
“…We identified Rad52, Rad59, and RPA as sumoylated proteins required for relocation of the collapsed fork caused by a CAG repeat to the NPC (Figure 1) [51]. Mutating the sumoylation sites on Rad52 (rad52-3KR) and Rad59 (rad59-2KR) [76] or RPA (rpa-6KR or rfa1-4KR) [77] led to a decrease in relocation. This decrease was more severe in a mutant that abolished the sumoylation of all three of these protein complexes (Rad52, Rad59, and all three subunits of RPA) [51].…”
Section: How Does Sumoylation Mediate the Movement Of Collapsed Forksmentioning
confidence: 96%